The relationship of the heart rate deflection point to the ventilatory threshold in trained cyclists - Bodner, M. E.; Rhodes, E. C.; Martin, A. D.; Coutts, K. D. (The Journal of Strength and Conditioning Research, 2002)
The purpose of this study was to assess the relationship of the heart rate deflection point (HRDP) to the ventilatory threshold (VT) in trained cyclists. Twenty-one endurance-trained cyclists (mean +/- SD: Vo(2)max = 67.6 +/- 4.7 ml x kg x min(-1)) completed a maximal cycle ergometer test of volitional fatigue using a ramped protocol. Ventilatory variables (Ve, Vo(2), Vco(2)) and power were measured online with averages reported every 20 seconds. Heart rate (HR) was recorded every 20 seconds using a Polar monitor. VT was calculated using the excess CO(2) elimination curve. The first derivative of a logistic growth curve fit to the HR-power data produced the HRDP. No significant differences (p > 0.01) existed between HR values at HRDP (171.7 +/- 9.6 b x min(-1)) and VT (169.8 +/- 9.9 b x min(-1)) or between Vo(2) values at HRDP (53.6 +/- 4.2 ml x kg x min(-1)) and VT (52.2 +/- 4.8 ml x kg x min(-1)). But power values at HRDP (318.7 +/- 30.7 W) were significantly different (p < 0.01) from those at VT (334.8 +/- 36.7 W). There were significant relationships between HRDP and VT for the physiological variables of HR (r = 0.92, p < 0.001), Vo(2) (r = 0.72, p < 0.001), and power (r = 0.77, p < 0.001). These findings indicate that HR and Vo(2) at HRDP are not significantly different from the values at VT in trained cyclists. HR values derived from HRDP may be used to set parameters for training intensity. Variability in the speed/power-HRDP relationship across detrained/trained states may be used to evaluate training programs.